In-situ preparation and electrochemical characterization of submicron sized NaFePO4 cathode material for sodium-ion batteries. (10th April 2017) - Heubner, C.; Heiden, S.; Schneider, M.; Michaelis, A.
Abstract : Graphical abstract: Abstract : Highlights: Preparation of submicron sized NaFePO4 by alkali metal cation displacement Significant composition dependence of kinetic and thermodynamic parameters Electrochemical properties correlate with asymmetric phase transition behavior The results support the recently reported path dependence of this system Abstract: Submicron sized NaFePO4 is successfully prepared in-situ by electrochemical delithiation of olivine type LiFePO4 and subsequent sodium insertion in aprotic electrolyte. The composition dependence of the Gibbs energy and the entropy of sodiation is investigated by temperature dependent measurements of the equilibrium potential. The exchange current density and the sodium-ion diffusion coefficient of NaFePO4 are systematically investigated as a function of the composition. Significant state of charge dependencies of the kinetic and thermodynamic parameters are found to correlate with phase transformations of the active material during charging and discharging. The results confirm the existence of a path dependence related to an asymmetric phase transformation behavior that was recently proposed in literature.